Research ethics : a philosophical guide to the responsible conduct of research - Comstock, Gary (Cambridge ; New York : Cambridge University Press, 2013)
"Ordinarily, responsible conduct of research (RCR) 'training' consists of lectures accompanied by generic exercises on 'core' topics. Research Ethics takes a novel, philosophical approach to the RCR and the teaching of moral decision-making. Part I introduces egoism and explains that it is in the individuals own interest to avoid misconduct, fabrication of data, plagiarism and bias. Part II takes up contractualism and covers issues of authorship, peer review and responsible use of statistics. Part III introduces moral rights as the basis of informed consent, the use of humans in research, mentoring, intellectual property and conflicts of interests. Part IV uses two-level utilitarianism to explore the possibilities and limits of the experimental use of animals, duties to the environment and future generations, and the social responsibilities of researchers. This book replaces mind-numbing rote exercises with an adventure in moral imagination and is an essential guide for graduate students in all disciplines"--
Machine generated contents note: Introduction; Part I. Protect my Interests: 1. Report misconduct; 2. Avoid plagiarism; 3. Beware intuition; 4. Justify decisions; Part II. Promote our Interests: 5. Articulate reasons; 6. Write cooperatively; 7. Protect manuscripts; 8. Clarify statistics; Part III. Respect Strangers' Rights: 9. Inform subjects; 10. Mentor inclusively; 11. Recognize property; 12. Reveal conflicts; Part IV. Honor All Interests: 13. Treat humanely; 14. Preserve environments; 15. Cultivate responsibility; Conclusion
Includes bibliographical references and index
10 13
Keywords: Science -- ethics; Ethics, Research